Derivation and external validation of dendritic cell-related gene signatures for predicting prognosis and immunotherapy efficacy in bladder urothelial carcinoma - An, Bingzheng; Guo, Zhaoxin; Wang, Junyan; Zhang, Chen; Zhang, Guanghao; Yan, Lei (Frontiers in Immunology, 2022)
Abstract Background: In the regulation of tumor related immunity, dendritic cells (DCs) are crucial sentinel cells, they are powerful to present antigens and initiate immune responses. Therefore, we concentrated on investigating the DC-related gene profile, prognosis and gene mutations in bladder urothelial carcinoma (BLCA) patients to identify sensitivity to immunotherapy of patients. Methods: According to the DCs infiltration, BLCA patients were divided into 2 subgroups, and differentially expression genes (DEGs) were obtained. Patients were classified by unsupervised clustering into new subgroups. The least absolute shrinkage and selection operator (LASSO) regression analysis and Cox regression was used to develop DC-related risk model, The CIBERSORT, XCell and GSEA were used to infer immune cells relative abundance separately and enriched immune pathways. Results: Totally, 29 prognosis-related DEGs were identified from the unsupervised cluster. Among them, 22 genes were selected for constructing a DC-related risk model. The DCRS can accurately distinguish patients with different sensitive response to immunotherapy and overall survival outcomes. Furthermore, The patients with ryanodine receptor 2 (RYR2) mutation had a better prognosis. Conclusions: The DCRS played a essential part in immunity pathway and formation of TME diversity. Our study indicated that RYR2 mutation combined with DCRS are useful for predicting the prognosis and discover appropriate patients for immunotherapy.